Database for the semi-rigid behaviour of beam-to-column connections in seismic regions - Cruz, P. J. S. (1998)
http://www.sciencedirect.com/science/article/B6V3T-3W7PSCR-4T/1/80e5bff184b2a8b2dbaef33032e7a577